607Longitudinal weight gain and lifestyle factors in women with and without polycystic ovary syndrome. (2nd September 2021) - Awoke, Mamaru Ayenew; Earnest, Arul; Joham, Anju; Hodge, Allison; Brown, Wendy; Teede, Helena; Moran, Lisa
Abstract: Background: Women with polycystic ovary syndrome (PCOS) have a higher prevalence of overweight/obesity and greater weight gain than women without PCOS. The association of lifestyle factors with weight change in PCOS is not known. Methods: We used data from the 1973-78 birth cohort of the Australian Longitudinal Study on Women's Health collected from seven surveys over 19 years (N = 14127 survey 1). Linear mixed-effects models were used to examine associations between diet, physical activity, and sitting time with weight change, after adjustment for socio-demographics, psychological factors, and health care utilisation. Results: Women with PCOS gained more weight annually (0·26 kg/year, 95% CI 0·13, 0·39; P < 0·0001) and over 19 years (4·75 kg; 95% CI 3·17, 6·34; P < 0·0001) than women without PCOS (adjusted analyses). For all women, there were positive associations between weight gain and energy intake, sitting time, and stress; inverse associations with fibre intake and physical activity; and no associations with diet quality, glycemic index, healthcare utilization, depression, or anxiety. There were interactions between lifestyle factors (energy intake P = 0·006, glycemic index P = 0·007, sitting time P = 0·029, and physical activity P = 0·022), PCOS status and time (age) such that weight gain varied between women with and without PCOS according to these factors. Conclusions: Women with PCOS had a higher rate of weight gain than women without PCOS. This was most marked in those with indicators of unhealthy lifestyles. Increased stress, energy intake and sitting time and lower physical activity contributed to weight gain in women with and without PCOS. Key messages: The findings reinforce the importance of early and ongoing lifestyle intervention and the potential use of specific lifestyle factors for weight gain prevention and management in PCOS.